(untitled) (Research, Society and Development, 2021)
The RC rotator cuff is formed by the supraspinatus, subscapularis, infraspinatus, and teres minor tendons. Since all tendons originate from the anterior and superior part and the posterior part of the shoulder region. The tendon structure is formed by six to nine structurally independent bundles, and by water and type I collagen. Objective: The aim of the present study was to determine whether muscle strengthening is effective in rotator cuff tendinopathy. Methods: The literature review was carried out in the virtual databases Pubmed and PEDro. The descriptors used were the following: Strengthening exercises; physiotherapy; Rotator cuff tendinopathy. Studies should meet the following eligibility criteria: articles published in English, publication interval of five years, between 2017 and 2021, randomized clinical trials, with a score greater than 6 on the PEDro quality scale. Results: 96 articles were found, with only 7 articles related to the topic. Conclusion: This literature review study verified the effectiveness of muscle strengthening in CR Tendinopathy, in all included studies, eccentric FM exercises and stretching obtained great results, from the period of pain to functionality and total mobility of each participant , however, it is extremely important to obtain further studies in order to outline new ways of treating tendinopathy in the rotator cuff.